Exploring Benefits for Tibetan Cleft Lip and Palate Recipient Families From the Social Perspective of Healthcare Linkage - Jing Lin; Xiao Qiong Teng; Chen Xin Zhang; Jing Peng; Jun Yi Guo (Health Expectations)
ABSTRACT Objectives To understand the psychological characteristics and actual sense of benefit of children with cleft lip and palate (CLP) and their caregivers who participated in social welfare medical activities in Tibet, and to promote the humanistic care and quality of medical services provided by healthcare workers in conjunction with social forces. Design Qualitative research through interviews and group discussions. Sample: Interviews with 13 participants in the medical activities for Tibet. Measurements: Thematic analysis. This paper adheres to the Consolidated Criteria for Reporting Qualitative Research (COREQ). Results The actual benefits perceived by CLP children and their caregivers who participated in the Tibetan social welfare medical activities could be summarized into five themes, Awareness of Aid Activities, Major Difficulties Faced by Affected Children and Families, Perceptions of Medical Assistance, Benefits of Participating in Medical Aid, and Expectations for Future Aid Activities. Conclusion Tibetan families with CLP children have benefited from this medical aid program, but there are many problems. It is necessary to increase the cultivation of humanistic and professional qualities of healthcare professionals and to call for and promote more social forces to play the role of healthcare and social teamwork. Patient or Public Contribution In our study, we placed a high value on the participation of patients and the public. During the research design phase, we organized a series of focus group discussions, inviting participants to share their experiences and needs, which helped us more precisely define the research questions and objectives. In the data analysis phase, we established a research discussion group consisting of researchers from diverse backgrounds to ensure that our findings aligned with the actual experiences of patients. Additionally, in the process of writing this manuscript, we also invited experienced senior medical and healthcare professionals to review the document, ensuring that the language used was patient‐friendly and that the content was closely aligned with patient concerns.